Restriction endonuclease banding and digestion resistant heterochromatin in triatomines, genus Panstrongylus - Tartarotti, Ester [UNESP]; Vilela de Azeredo-Uliveira, Maria Tercilia [UNESP] (Firenze University Press, 2000)
The present work realized a comparative study in meiosis of two triatomines, Panstrongylus herreri and P. megistus, by cytogenetic techniques involving the restriction endonucleases Hae III and Alu I and C-banding. The system of sex chromosomes in Panstrongylus is of the X1X2Y type, and experiments corroborated the common origin hypothesis of the X chromosomes by fragmentation of single X. In both species the restriction endonucleases (RE) presented banding patterns in part similar to C-banding. However, in some early meiotic phases it was possible to verify differentiation of the heterochromatic pattern. This work suggests that other elements besides presence of recognition sites, such as chromatin packing degree and DNA-protein interaction, act in RE results, since digestion patterns occur in early spermatogenesis. However, metaphase chromosomes were practically inaccessible to the endonucleases.
Keywords: C-band; Cytogenetic; Restriction endonucleases; Spermatogenesis; Triatomines